Gödslingsstrategins inverkan på Holmen Skog, Umeå distrikt - Thelberg, Erik (2011)
This thesis analyzes the effects of different fertilization strategies on forest management at Holmen Skog in Umeå district. Harvesting volumes, net present values and fertilization intensity are presented for each fertilization scenario. The planning reserve (percentage area older than minimum final felling age) was also analyzed in this study. The thesis covers the analysis of five different fertilization scenarios, varying in fertilization intensity, from no fertilization at all, to fertilization at every harvesting operation (thinning or final felling). A sub-study was also carried out so the reader in detail can see how the different fertilization scenarios affect individual forest stands of different nature. The analysis has been done with the planning tool PlanWise, which is an application of the Heureka analysis and planning system. Of the analyzed scenarios it is most profitable to fertilize as much as possible, at each harvesting operation or twice before final felling. Among the analyzed scenarios, both net present value and harvesting volumes are higher the more the forest is fertilized. The size of the planning reserve has a relatively large impact on forest management. A low planning reserve results in a higher harvest volume already today compared to the current harvest level. A high planning reserve brings about low harvest volumes at the beginning of the of the planning periodas old forest must be saved to obtain a certain level of the planning reserve. Compared to a low reserve a high reserve also leads to net present value losses but has the advantage that the planning of harvesting operations is facilitated.